The association of hemoglobin levels and balance function in patients with stroke: a multicenter study in China - Zhu, Jie; Bi, Ranran; Zhang, Shuyang; Lin, Yansheng; Lin, Yifang; Zhao, Xuezhen; Lin, Jiali; Jia, Jie (Frontiers in Neuroscience, 2026)
BackgroundBalance impairment following stroke is a leading cause of disability and falls. Hemoglobin (Hb) affects systemic and cerebral oxygen delivery and may influence neuromuscular function and post-stroke balance, but evidence from large multicenter clinical samples is limited. We investigated the association between hemoglobin concentration and balance performance in a Chinese multicenter cross-sectional study of stroke patients.MethodsWe studied 2,006 neuroimaging-confirmed stroke patients from 26 hospitals. Balance impairment was defined as BBS ≤ 40. Admission Hb (g/dL) was analyzed per 1 g/dL and by tertiles (<12.6 g/dL, 12.6–14.0 g/dL, ≥14.0 g/dL). Multivariable logistic regression with sequential adjustment, restricted cubic splines, and prespecified subgroup and sensitivity analyses evaluated associations.ResultsBalance impairment occurred in 70.5% (1,414/2,006). Each 1 g/dL higher Hb was associated with lower odds of impairment in unadjusted (OR 0.83, 95% CI 0.78–0.87; p < 0.001) and fully adjusted models (OR 0.89, 95% CI 0.83–0.96; p = 0.002). This association remained robust after comprehensive adjustment for demographic, lifestyle, comorbidity, stroke characteristics, and lesion location factors. Compared with the lowest tertile, adjusted ORs were 0.72 (95% CI 0.53–0.99; p = 0.042) for the middle tertile and 0.62 (95% CI 0.45–0.85; p = 0.003) for the highest tertile. Spline analyses suggested a broadly linear inverse association; results were consistent across subgroups and sensitivity checks.ConclusionHigher admission hemoglobin was independently associated with better balance after stroke. Prospective studies should test whether Hb optimization improves rehabilitation outcomes.